2011
DOI: 10.1002/etc.490
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity, histopathology, and coagulopathy in American kestrels (Falco sparverius) following administration of the rodenticide diphacinone

Abstract: The acute oral toxicity of the anticoagulant rodenticide diphacinone was found to be over 20 times greater in American kestrels (Falco sparverius; median lethal dose 96.8 mg/kg body weight) compared with Northern bobwhite (Colinus virginianus) and mallards (Anas platyrhynchos). Modest evidence of internal bleeding was observed at necropsy, although histological examination of heart, liver, kidney, lung, intestine, and skeletal muscle revealed hemorrhage over a wide range of doses (35.1-675 mg/kg). Residue anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 27 publications
1
74
1
Order By: Relevance
“…Similarly, bromadiolone and brodifacoum were the two most common compounds found in more than 100 mountain lions tested from around the state of California (R. H. Poppenga, personal communication, December 8, 2010). Respondents also reported use of the first-generation anticoagulant poison diphacinone, but this chemical is also highly toxic to birds and mammals (Rattner et al 2011). …”
Section: San Fernando Valleymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, bromadiolone and brodifacoum were the two most common compounds found in more than 100 mountain lions tested from around the state of California (R. H. Poppenga, personal communication, December 8, 2010). Respondents also reported use of the first-generation anticoagulant poison diphacinone, but this chemical is also highly toxic to birds and mammals (Rattner et al 2011). …”
Section: San Fernando Valleymentioning
confidence: 99%
“…In turn, opportunistic predators may be at a particular risk because they seek prey that can be caught easily. Consumption of either prey or carcasses contaminated with rodenticides may lead to poisoning of a predator (Brakes and Smith 2005;Rattner et al 2011). SGARs can even affect wildlife as a result of consuming contaminated invertebrates, contaminated soil, or baits that have been removed from bait stations by rodents (Dowding et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For raptors (Falconiformes, Strigiformes), it has been shown that they are more sensitive to the rodenticide diphacinone than the bobwhite quail, one of the most commonly used model species in avian toxicity testing (Rattner et al 2011). For corvids, to our knowledge, no toxicity data are available in literature but different elements suggest that they could be less sensitive to anticoagulants than raptors.…”
Section: Composition Of Scavenger Community and Relative Risk Betweenmentioning
confidence: 97%
“…For acute risk assessment, in the absence of data specific to raptors and corvids, we used the LD50 of 138 mg of bromadiolone/kg bw determined for the bobwhite quail Colinus virginianus to calculate TER (European Food Safety Authority 2010). For the short-term risk and in the absence of toxicity data for the studied raptor species, the LD100 of the great horned owl Bubo virginianus following a 1-week exposure was used: 0.056 mg of bromadiolone/kg bw/d (European Food Safety Authority 2010), the high difference between acute and short-term toxicity for birds reflecting the magnification of rodenticide toxicity following repeated exposure (Joermann 1998) and differences in interspecies sensitivity (Rattner et al 2011). In every cases, an acute risk was not evidenced as the TER was always much higher than ten, while a short-term exposure of 1 week would represent a high risk of secondary poisoning for both corvids and raptors (Table 2).…”
Section: Composition Of Scavenger Community and Relative Risk Betweenmentioning
confidence: 99%
“…Once ingested, vitamin K is physiologically processed for the production of blood clotting proteins, which gives vitamin K (in particular, Vitamin K1 and K2; Tasheva 1995) the ability to counteract anticoagulant compounds (e.g., Mackintosh et al 1988;Tasheva 1995). Anticoagulant rodenticides irreversibly inhibit the enzyme vitamin K epoxide reductase that is necessary for posttranslational carboxylation of the prothrombin group of serine protease coagulation factors; without the carboxyl group these factors do not assemble on cell surfaces to form active coagulation complexes (Rattner et al 2011). There are several chemical formulations of vitamin K, all of which are required in metabolic activity in the liver where blood-clotting proteins are synthesized (Robbins 1993;Tasheva 1995).…”
Section: Introductionmentioning
confidence: 98%